Media education - the basis of forming a culture of personality and a means of protecting young people from the impact of negative media content (Pedagogy of Higher and Secondary Education, 2012)
Burím O. V. Media education - the basis of forming a culture of personality and a means of protecting young people from the impact of negative media content.The article is devoted to the problem of media education's introduction in the Ukraine. The author considers the essence of media education as a foundation of the personality’s culture forming in the modern information society and the means of young people’s protection from the destructive media effects.
Keywords: destructive influence; media effects; media education; media literacy; media competence; media content